Biocompatibility of New Calcium Aluminate Cement: Tissue Reaction and Expression of Inflammatory Mediators and Cytokines - Roberti Garcia, Lucas da Fonseca [UNESP]; Huck, Claudia [UNESP]; Oliveira, Leticia Menezes de [UNESP]; Chaves de Souza, Pedro Paulo [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Elsevier B.V., 2014)
Introduction: The aim of this study was to evaluate the biocompatibility of a new calcium aluminate cement (EndoBinder) in subcutaneous tissue of rats in comparison with mineral trioxide aggregate and calcium hydroxide hard-setting cement. Methods: Polyethylene tubes (1.5 x 10 mm) containing the dental cements were implanted into dorsal subcutaneous tissue of 30 rats. After experimental periods of 7, 30, and 90 days, biopsies were performed for tissue response analysis under optical light microscope. The mRNA extraction was performed for molecular evaluation of the inflammatory process in the peri-implant tissue, which was submitted to quantitative real-time polymerase chain reaction analysis for inflammatory mediators and cytokines TNF-alpha, Ptges2,11-1 beta,11-4, and 11-10. Results: On the basis of the score used to grade the tissue reaction (0-3), EndoBinder (0) presented no inflammatory reaction after the 90-day period, a similar result to mineral trioxide aggregate and calcium hydroxide. The thickness of inflammatory capsules (mu m) also presented significant decrease during the course of periods (P < .05). As regards expression of inflammatory mediators, Ptges2 and 11-10 were detected only at 7 and 30 days, with no statistically significant difference among the experimental groups (P> .05). Conclusions: EndoBinder induced limited inflammatory reaction. It was considered biocompatible when tested in subcutaneous tissue of rats.
Keywords: Biocompatibility; calcium aluminate cement; calcium hydroxide; mineral trioxide aggregate; tissue reaction